2000
DOI: 10.1046/j.1460-9568.2000.00296.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high frequency stimulation of subthalamic nucleus on extracellular glutamate and GABA in substantia nigra and globus pallidus in the normal rat

Abstract: High frequency stimulation (130 Hz) of the subthalamic nucleus has dramatic beneficial motor effects in severe parkinsonian patients. However, the mechanisms underlying these clinical results remain obscure. The objective of the present work was to study the neurochemical changes induced in rats by high frequency stimulation of the subthalamic nucleus by using intracerebral microdialysis within its target structures. Our results show that high frequency stimulation of the subthalamic nucleus induces a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
221
2
6

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(257 citation statements)
references
References 24 publications
28
221
2
6
Order By: Relevance
“…During STN HFS in human subjects with Parkinson's disease (PD), Stefani et al 50,51 detected an increase in pallidal cGMP, considered to be a secondary messenger in the glutamatergic signaling pathway, which was accompanied by improvement in clinical symptoms. Microdialysis studies during STN HFS in normal anesthetized rats detected elevated levels of 1) glutamate in both the substantia nigra pars reticulata (SNr) and the GP (rat analog of primate GPe), which is consistent with increased output from STN, 52,53 and 2) GABA in the SNr, which may be a secondary effect or a result of suprathreshold current spreading into pallidonigral fibers of passage. 54 These studies have also shown that elevated GABA levels depend on the frequency of stimulation, closely mimicking the frequency-response curves reported in clinical applications of DBS.…”
Section: Axonal Output Of the Stimulated Nucleusmentioning
confidence: 79%
“…During STN HFS in human subjects with Parkinson's disease (PD), Stefani et al 50,51 detected an increase in pallidal cGMP, considered to be a secondary messenger in the glutamatergic signaling pathway, which was accompanied by improvement in clinical symptoms. Microdialysis studies during STN HFS in normal anesthetized rats detected elevated levels of 1) glutamate in both the substantia nigra pars reticulata (SNr) and the GP (rat analog of primate GPe), which is consistent with increased output from STN, 52,53 and 2) GABA in the SNr, which may be a secondary effect or a result of suprathreshold current spreading into pallidonigral fibers of passage. 54 These studies have also shown that elevated GABA levels depend on the frequency of stimulation, closely mimicking the frequency-response curves reported in clinical applications of DBS.…”
Section: Axonal Output Of the Stimulated Nucleusmentioning
confidence: 79%
“…Alternatively, it is possible that high-frequency GPi activity develops under HFS of STN because HFS drives the efferent axons projecting from the site where it is applied, augmenting neurotransmitter release, as argued by Montgomery and Baker (2000). It has been shown, for example, that HFS of STN in normal rat leads to an increase in extracellular glutamate in GPi and the substantia nigra pars reticulata (SNr), to which STN is the primary source of excitatory afferents (Paul et al, 2000;Windels et al, 2000). This theory is also supported by studies in parkinsonian patients, which found inhibitory effects after microstimulation of GPi (Dostrovsky et al, 2000), as well as increases in blood oxygenation level-dependent signal in subcortical regions in functional magnetic resonance imaging during DBS of STN, suggesting overstimulation of STN targets (Jech et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of recent experiments have called this viewpoint into question, however, by demonstrating that high-frequency stimulation (HFS) leads to enhanced activity in stimulated areas (Garcia et al, 2003) or downstream effects consistent with enhanced synaptic outputs from stimulated areas (Paul et al, 2000;Windels et al, 2000;Anderson et al, 2003;Hashimoto, 2003). This leads to a theoretical conundrum, as it is not at all clear how to explain the beneficial effects of DBS if its action is to enhance neuronal activity.…”
Section: Introductionmentioning
confidence: 99%
“…Although the therapeutic outcome is similar for both these interventions, the mechanisms underlying STN lesioning and stimulation may be different (McIntyre et al, 2004a,b). Indeed, evidence from experimental animal models has suggested that neurochemical and physiologic changes with stimulation at the target site may not be explained simply by inhibition (Windels et al, 2000;Hashimoto et al, 2003). Nonetheless, neural recordings during DBS in awake patients have indicated that local inhibition is an important feature of therapeutic DBS (Dostrovsky and Lozano, 2002).…”
Section: Metabolic Changes With Stn Stimulationmentioning
confidence: 99%